2014
DOI: 10.3354/meps10889
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the skeletal mineralogy of temperate bryozoans: the relative influence of environmental and biological factors

Abstract: Bryozoans exhibit a highly variable geochemistry within their calcium carbonate skeletons. Previous studies have predominantly attributed this variability to differences in seawater temperature influencing the relative deposition of aragonite and calcite, and the extent of magnesium incorporation into the calcite lattice. However, the patterns and scale of this variability have not been examined in detail. We conducted a high-replicate, multi-site study on the skeletal mineralogy of temperate Northern Hemisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…All of the bryozoans from Langkawi and Penang are shore samples of colonies from very shallow water (<10 m), whereas many of the bryozoans reported in previous publications came from mid-to outer shelf depths. Analyses of bryozoan assemblage mineralogy relative to depth on the continental shelf are lacking, although Loxton et al (2014) found a positive correlation between depth and the proportion of aragonite in skeletons of the bimineralic cheilostome Microporella ciliata (Pallas, 1766) in NE Scotland. The generality of this trend within and among species is unknown but if applied to the latitudinal comparisons made here more aragonite would be expected in bryozoans from deeper parts of the Malaysian shelf and the contrast with regions of higher latitude would be even greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the bryozoans from Langkawi and Penang are shore samples of colonies from very shallow water (<10 m), whereas many of the bryozoans reported in previous publications came from mid-to outer shelf depths. Analyses of bryozoan assemblage mineralogy relative to depth on the continental shelf are lacking, although Loxton et al (2014) found a positive correlation between depth and the proportion of aragonite in skeletons of the bimineralic cheilostome Microporella ciliata (Pallas, 1766) in NE Scotland. The generality of this trend within and among species is unknown but if applied to the latitudinal comparisons made here more aragonite would be expected in bryozoans from deeper parts of the Malaysian shelf and the contrast with regions of higher latitude would be even greater.…”
Section: Discussionmentioning
confidence: 99%
“…The mineralogy of the bryozoan skeleton is under a high degree of organismal control (Smith 2014;, although bimineralic species may exhibit apparent ecophenotypic variability in the proportions of calcite and aragonite in their skeletons (e.g. Lombardi et al 2008;Loxton et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The biological or ''vital effect'' is a time-independent offset from theoretical/experimental equilibrium and thermodynamics controlled by physiological processes. Many organisms exert a certain level of control on CaCO 3 precipitation as identified in previous studies of foraminiferans (e.g., Bentov & Erez, 2006), corals (e.g., Marshall, 1996;Tambutt e et al, 1996), bivalves (e.g., Kennedy et al, 1969), gastropods (e.g., Nehrke & Nouet, 2011;Yao et al, 2010), and bryozoans (e.g., Loxton et al, 2014). As a consequence, it is essential to consider biological controls in the use of biogenic materials as proxies for environmental reconstruction (e.g., Austin & James, 2008, and references therein).…”
Section: Introductionmentioning
confidence: 90%
“…Kukliński & Taylor ; Loxton et al . ). Marine bryozoans are usually stenohaline, but some unskeletonized ctenostomes can tolerate brackish conditions.…”
mentioning
confidence: 97%
“…Water temperature also influences the chemical composition of bryozoan skeletons, generally by increasing the Mg content with increasing temperature (e.g. Kukli nski & Taylor 2008;Loxton et al 2014). Marine bryozoans are usually stenohaline, but some unskeletonized ctenostomes can tolerate brackish conditions.…”
mentioning
confidence: 99%